Análisis de la centralización de los tribunales anticorrupción en la ciudad de Quito - León Burgos, José Eduardo (2025)
In the fight to combat corruption and related crimes, many countries have created specialized anti-corruption courts that are distinguished from ordinary judicial institutions. In 2021, the Judiciary Council ordered the creation of the only headquarters in the capital of Ecuador. This investigative work analyzes how centralization in Quito can violate constitutional rights in Ecuador; the exclusivity of these courts in a single location raises questions about equity and justice in legal processes related to corruption. The judges will act in relation to crimes against: Humanity, The rights of freedom, The rights of property, The efficiency of public administration, Economic crimes, The illicit production or trafficking of scheduled substances subject to control, Mining resources, Against the structure of the constitutional state, Terrorism and financing. There are three arguments in favor of specialized anti-corruption courts: efficiency, integrity and experience. The most common reason for establishing a specialized court is the desire to improve efficiency in the treatment of anti-corruption cases. The lack of judicial efficiency can be particularly pernicious in corruption cases for two reasons: the urgency of making progress in the fight against corruption, and the significant delays in cases. The findings indicate that the exclusivity of the court created in Ecuador has a positive aspect in terms of the desire for justice, but it presents deficiencies in terms of equitable access to justice and respect for constitutional rights. It could generate inequalities in access. To justice for people who do not reside in the capital, this could violate the principle of equality before the law enshrined in the Ecuadorian constitution. Centralization not only affects the accused.